Educação no meio rural em Piracanjuba/GO : a escola municipal de educação básica urbano Pedro Guimarães - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The present research has as main objective to analyze the national and state educational guidelines and policies of the Field Education and its implementation in the Municipal Education Network in Piracanjuba, state of Goiás, highlighting the process of its implementation in the Municipal School of Basic Education Urbano Pedro Guimarães. The specific objectives aim to: 1) Emphasize the importance of public educational policies in the countryside and how they structure education in the countryside in Goiás and in the municipality of Piracanjuba; 2) To discuss the educational guidelines adopted in the municipal school network in Piracanjuba and the conceptions of education for the schools located in the field, and finally; 3) To present the conceptions and visions of the educational management, the school managers and the teachers about the theme of the Field Education. The methodology used in this research is based on three distinct moments, but articulated among them: Theoretical Research, Documentary Research and Field Research. The Master Dissertation is structured in three chapters that deal with the Field Education and how it has been developed and / or applied in the researched school unit, in view of the current municipal, state and federal legislation. In this sense, this research aims to contribute to the discussion about the importance of applying the presumptions of the education of the field to the schools in the field, with a focus for the future implantation in the Municipal School of Basic Education Urbano Pedro Guimarães.
Keywords: Políticas Educacionais do Campo; Educação do Campo; Rede Municipal de Ensino; Escola no Campo; Field Educational Policies; Field Education; Municipal Network of Education; School in the Field; CIENCIAS HUMANAS::EDUCACAO; OUTROS